Effects of electron beam irradiation on microbial loads, physicochemical properties, stability of active ingredients, and antioxidant activity in Angelica sinensis Radix - Yunxia Hu; Haijun Wang; Zhijun Xin; Wensheng Gou; Zhuanzi Wang; Xiao Liu; Xihong Lu; Aimei Yang; Xuehu Li; Libin Zhou (Journal of Agriculture and Food Research)
As the demand for safe, wholesome, and high-quality food continues to rise, more research is being done on innovative food processing technologies that maximize efficiency while reducing negative effects on food quality. This study evaluates electron beam irradiation (EBI), a non-thermal green technology, for its microbial inactivation efficacy and quality preservation effects on Angelica sinensis Radix (A. sinensis). The investigation tested EBI doses from 0 to 10 kGy, revealing dose-dependent microbial reduction at 4–10 kGy and effective color retention at 2–6 kGy. GC-MS analysis revealed that EBI did not alter the chemical diversity of volatile organic compounds (VOCs) in A. sinensis but induced variations in their relative abundances. Orthogonal partial least squares discriminant analysis (OPLS-DA) coupled with variable importance in projection (VIP) scores identified potential biomarkers for discriminating irradiation doses. Notably, key bioactive components, including ligustilide and senkyunolide I/H, remained stable across all tested doses. However, the volatile oil, total phenolic, chlorogenic acid and ferulic acid contents in the 10 kGy group exhibited increases of 7.14 %, 12.18 %, 5.37 %, and 6.28 %, respectively, compared to the control. Antioxidant activity remained elevated post-irradiation, correlating with the enrichment trends of volatile oil and phenolic acids. Based on these findings, the study proposes 4 kGy as the optimal EBI dose for balancing microbial control with quality retention. Meanwhile, 10 kGy irradiation enhances active compound release, providing high-quality raw materials for functional food and pharmaceutical applications. This multi-criteria evaluation framework advances standardized EBI protocols in traditional Chinese medicine processing.